2020
DOI: 10.3390/sym12061052
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in Football: The Pass—Goal Paradox

Abstract: We investigate the relation between the number of passes made by a football team and the number of goals. We analyze the 380 matches of a complete season of the Spanish national league “LaLiga" (2018/2019). We observe how the number of scored goals is positively correlated with the number of passes made by a team. In this way, teams on the top (bottom) of the ranking at the end of the season make more (less) passes than the rest of the teams. However, we observe a strong asymmetry when the analysis is made dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…We found that all passing indices for the matches between the first eight and the last eight were significantly greater than the matches between the first eight. This result is in accordance with a previous analysis that found that the top teams made more passes and scored more goals, while teams relegated to a lower level had, on average, a lower number of passes and goals [ 11 ]. However, there are also some studies showing that passing indices have a smaller contribution to ranking points obtained in a professional game [ 34 ] and are less predictable when considering team quality and home advantage [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that all passing indices for the matches between the first eight and the last eight were significantly greater than the matches between the first eight. This result is in accordance with a previous analysis that found that the top teams made more passes and scored more goals, while teams relegated to a lower level had, on average, a lower number of passes and goals [ 11 ]. However, there are also some studies showing that passing indices have a smaller contribution to ranking points obtained in a professional game [ 34 ] and are less predictable when considering team quality and home advantage [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 92%
“…The top teams in the season pass more times than other teams. The number of passes in the second half of the match was lower, but the number of goals was higher [ 11 ]. A comparison of the passing methods of Spain and South Korea, the champions of the 2010 World Cup in South Africa, found that there were significant differences in the number of short-passes in the first half and the number of short-passes, middle passes, long-passes, flat passes and direct passes in the second half [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A critical factor in predicting soccer match outcomes is successfully incorporating domain knowledge into the machine-learning modelling process 34 Building a standard linear model for an entire soccer team or subgroup, as in the APX-Grp approach, can be misleading and should be used cautiously and only when not enough individual data is available. We have encountered situations where the relationships in unique models contradict those that reveal joint modelling for the group, perfectly illustrating Simpson's paradox 35,36 . The experience reminds us to be careful when interpreting soccer data because relationships observed for a group of players usually refer to momentary relationships between players, not temporal relationships in player performances.…”
Section: Discussionmentioning
confidence: 87%
“…Specifically, shots on target are one of the best variables to discriminate between successful and unsuccessful teams [11 -13]. Also indicators of success are ball possession [14 -16], total number of shots [17 -19], ball retrieval location [20,21], number of passes and success rate of completed passes [11,18,19,22,23].…”
Section: Introductionmentioning
confidence: 99%